2005
DOI: 10.1111/j.1439-0396.2005.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of level of feed intake and Fusarium toxin‐contaminated wheat on rumen fermentation as well as on blood and milk parameters in cows

Abstract: The aims of this study were to examine the effects of and possible interactions between dry matter (DM) intake and feeding Fusarium toxin-contaminated wheat on ruminal fermentation, serum chemical parameters and milk yield of dairy cows. Fourteen dairy cows equipped with ruminal and duodenal cannulas were analysed. All animals were fed the same ration, the daily feed amounts being adjusted to current performance. On DM basis, the ration consisted of 60% concentrate including 55% wheat [Fusarium-contaminated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
6
30
2
Order By: Relevance
“…However, increased activity of serum AST and ALT are not always a clear indicator of liver disease, at all events for degenerative processes. Seeling et al 55 reported increased activities of serum AST, GLDH (glutamate dehydrogenase) and γ -GT (γ -glutamyl transferase) with increasing organic matter intake, which were not related to mycotoxin contamination of wheat.…”
Section: Serum Activity Of Hepatic Enzymesmentioning
confidence: 97%
“…However, increased activity of serum AST and ALT are not always a clear indicator of liver disease, at all events for degenerative processes. Seeling et al 55 reported increased activities of serum AST, GLDH (glutamate dehydrogenase) and γ -GT (γ -glutamyl transferase) with increasing organic matter intake, which were not related to mycotoxin contamination of wheat.…”
Section: Serum Activity Of Hepatic Enzymesmentioning
confidence: 97%
“…The data concerning the effects of mycotoxin-contaminated diets on health and performance of dairy cows are still rare. Studies by Danicke et al (2005), and Seeling et al (2006) showed that DON concentrations ranging between 3.1 and 3.5 mg g -1 feed (88% DM) did not cause any significant adverse health effects but transiently increased post-prandial ammonia concentrations (Fink Grammels 2008). Fink Grammels (2008) found correlation between the capacity of the rumen to inactivate mycotoxins and the likelihood of adverse health effects in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…De-epoxide is far less toxic, which explains the animals tolerance to the presence of this substance in feed. In animals with a previous history of ruminal acidosis, DON is not fully broken down, and its presence is determined in the blood (Seeling et al 2006). Grass haylage contaminated with deoxynivalenol causes the toxic syndrome in cattle, which is characterized by more pronounced inflammations, enteritis, mastitis and laminitis (Weaver et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Every change in feeding regime should eliminate suspected contaminants, such as mycotoxins, from feed, unfortunately, such practices often introduce new contaminating agents. Lactating cows are more susceptible to infections caused by feed-borne mycotoxins than beef cattle due to their very high performance levels (Seeling et al 2006, Gajęcki 2010.…”
Section: Introductionmentioning
confidence: 99%